2023
DOI: 10.1002/nop2.1782
|View full text |Cite
|
Sign up to set email alerts
|

Nurse educators' suggestions for a digital educational resource suitable for undergraduate student nurses' placement studies: Qualitative empirical research

Abstract: Aims To explore and describe nurse educators' suggestions regarding a digital educational resource addressing quality in placement studies for first‐year student nurses in nursing homes. Design A qualitative, explorative, and descriptive research design. Methods Focus group interviews with eight nurse educators and individual interviews with six nurse educators. The interviews were audio‐recorded and transcribed verbatim; subsequently, data were analysed in lines with content analysis as described by Graneheim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Nurse educators experienced the interactive communication features of the digiQUALinPRAX resource as a valued component, as it enhanced their ability to provide written feedback on students’ submissions for their learning processes. This finding is also important, as earlier research [ 42 , 43 ] has revealed that many students received insufficient written feedback on their submissions from nurse educators during clinical placement education. This inappropriate feedback may have a negative influence on students’ learning experiences, whereas it might hinder them in their ability to identify areas in which they need to improve and further study to close their gap in knowledge [ 43 ].…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Nurse educators experienced the interactive communication features of the digiQUALinPRAX resource as a valued component, as it enhanced their ability to provide written feedback on students’ submissions for their learning processes. This finding is also important, as earlier research [ 42 , 43 ] has revealed that many students received insufficient written feedback on their submissions from nurse educators during clinical placement education. This inappropriate feedback may have a negative influence on students’ learning experiences, whereas it might hinder them in their ability to identify areas in which they need to improve and further study to close their gap in knowledge [ 43 ].…”
Section: Discussionmentioning
confidence: 90%
“…This forum played a vital role in facilitating interactions between students and the stakeholders involved in overseeing and supervising students during their nursing home placement. Previous research supports the notion that this interactive design feature, integrated into digital educational resources, is essential for effectively implementing and utilising technology to enhance student supervision [ 20 , 42 , 59 ]. Notably, the presence of such dialogue forums, which enables interaction among stakeholders, has been reported as an indicator of satisfaction with digital educational resources [ 20 ].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations